English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

If k also equals the product of a^b and c^b, then c equals:

2006-11-24 12:09:54 · 3 answers · asked by victoria 1 in Science & Mathematics Mathematics

3 answers

So k = (a^2)^(3b) = a^(2 * 3b) = a^(6b).
We also know k = a^b * c^b.
So a^(6b) = a^b * c^b.
So a^(5b) = c^b.
So (a^5)^b=c^b.
So c = a^5.

2006-11-24 12:13:14 · answer #1 · answered by stephen m 4 · 0 0

Let k be the result of squaring the base and tripling the exponent of a^b, a>b>1.?
If k also equals the product of a^b and c^b, then c equals

k = (a^2)^(3b)
= a^(6b)
k = a^b.c^b

So a^(6b) = a^b.c^b
c^b = a^(6b)/a^b
= a^(6b)*a^(-b)
= a^5b
= (a^5)^b

Thus c = a^5

2006-11-24 21:28:35 · answer #2 · answered by Wal C 6 · 0 0

victoria They are Talking about you...!!
http://www.osoq.com/funstuff/extra/extra03.asp?strName=victoria

2006-11-24 20:39:54 · answer #3 · answered by mnd p 1 · 0 0

fedest.com, questions and answers